(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this qualitative study is to investigate the motivations and problems that smallscale food business owners experience when implementing digital marketing methods to promote healthy eating choices. With the growing popularity of digital platforms, small-scale food businesses are realizing the value of embracing digital marketing to reach a larger audience and promote their products and services. However, for small-scale food business owners, the use of digital marketing methods, particularly those aimed at promoting healthy food choices, brings distinct motives and problems. In-depth interviews will be conducted with a selection of small-scale food business owners who have included internet marketing into their promotional activities for this project. The interviews will delve into the factors that lead these business owners to implement digital marketing methods, such as improving brand visibility and responding to changing consumer expectations for healthier food options. Furthermore, the study will look at the issues that small-scale food business owners face when applying digital marketing techniques, such as limited finances, a lack of digital marketing skills, and difficulties presenting the health benefits of their goods effectively. The study’s findings will provide useful insights into the incentives and problems that small-scale food business owners encounter when implementing digital marketing methods to promote healthy food choices. The study will add to the existing literature by providing a more nuanced understanding of the factors that drive decision-making and the hurdles that small-scale food company owners confront. The highlighted motives and challenges can be used to build customized strategies, training programmers, and support systems to help small-scale food enterprises effectively integrate digital marketing into their operations in order to encourage healthy food choices.